2021
DOI: 10.36457/gizindo.v44i2.566
|View full text |Cite
|
Sign up to set email alerts
|

Overview of High Sodium Eating Habits Before and After Covid-19 Pandemic in Indonesia

Abstract: National and global reports showed a high prevalence of sodium intake above the recommended threshold. The pandemic situation might have altered people's eating habits into a healthier diet to improve the immunity system. A high-sodium diet, which has previously been reported as a substantial contributor to several degenerative diseases, might be considered unhealthy eating habits. This study aimed to analyze whether the Covid-19 pandemic has changed the eating habits of high sodium foods and drinks in college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…However, self-report of the respondents shows that consuming fried foods/high-fat foods 1 time/day. Similar study in Indonesia reports that some of the respondents still consume high sodium food and drinks, in the form of packaged foods or street food snacks during the COVID-19 pandemic [18].…”
Section: Discussionmentioning
confidence: 61%
“…However, self-report of the respondents shows that consuming fried foods/high-fat foods 1 time/day. Similar study in Indonesia reports that some of the respondents still consume high sodium food and drinks, in the form of packaged foods or street food snacks during the COVID-19 pandemic [18].…”
Section: Discussionmentioning
confidence: 61%
“…In a survey on dietary behaviors of college students in Indonesia studying from home during COVID-19, authors found an increase in the option of buying cooked food from online delivery services [ 46 ]. Another quantitative study among college students in Indonesia showed no significant decrease in consumption of packaged foods and sugar sweetened beverages during the pandemic in August 2020 compared to December 2019 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 also exacerbated existing chronic health conditions [ 18 ], and people with pre-existing chronic conditions had a higher risk for contracting COVID-19 [ 19 ]. More so, with a high level of uncertainty about the COVID-19 virus among scientists and epidemiologists, no vaccine, and no effective drug therapy during the active phase of the pandemic, nutrition was considered a robust preventive approach [ 1 , 20 , 21 , 22 , 23 ]. However, the evidence on the benefits of nutrition interventions on overall health outcomes during the COVID-19 in Indonesia is mixed [ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Makanan asin dan kemasan merupakan makanan yang mengandung tinggi natrium dan bahan penyedap rasa yang menyebabkan efek negative dalam metabolisme tubuh. 33,34 Penyedap rasa seperti monosodium glutamat (MSG) ditambahkan pada makanan untuk menambah rasa lezat dalam jangka panjang dapat merusak neuron pada nukleus dan menganggu penyampaian sinyal leptin. Hal ini akan menyebabkan resistensi leptin yang akan memperparah risiko obesitas.…”
Section: Bahasanunclassified